1999
DOI: 10.1016/s0960-9822(99)80169-9
|View full text |Cite
|
Sign up to set email alerts
|

A unique talin homologue with a villin headpiece-like domain is required for multicellular morphogenesis in Dictyostelium

Abstract: Molecules involved in the interaction between the extracellular matrix, cell membrane and cytoskeleton are of central importance in morphogenesis. Talin is a large cytoskeletal protein with a modular structure consisting of an amino-terminal membrane-interacting domain, with sequence similarities to members of the band 4.1 family, and a carboxy-terminal region containing F-actin-binding and vinculin-binding domains [1] [2]. It also interacts with the cytoplasmic tail of beta integrins which, on the external fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 29 publications
(35 reference statements)
2
59
0
Order By: Relevance
“…8D,G). It is thought that upper cup cells are especially important in the elevation of the spore mass from the substrate and it may be that these cells need to make especially strong cell-cell and possibly cell matrix contacts (Tsujioka et al, 1999). However, the rescue experiments where paxB was expressed from prestalk-and prespore-specific promoters showed that paxB expression needs to be expressed in prespore and prestalk cells to be able to achieve a complete rescue of development, especially slug migration, showing that all cells in the slug actively contribute to the migration of the slug.…”
Section: Paxb and Lim2 Have Nonredundant Roles In Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…8D,G). It is thought that upper cup cells are especially important in the elevation of the spore mass from the substrate and it may be that these cells need to make especially strong cell-cell and possibly cell matrix contacts (Tsujioka et al, 1999). However, the rescue experiments where paxB was expressed from prestalk-and prespore-specific promoters showed that paxB expression needs to be expressed in prespore and prestalk cells to be able to achieve a complete rescue of development, especially slug migration, showing that all cells in the slug actively contribute to the migration of the slug.…”
Section: Paxb and Lim2 Have Nonredundant Roles In Developmentmentioning
confidence: 99%
“…Actin-rich membrane fragments are left behind by migrating cells (Uchida and Yumura, 2004). Dictyostelium contains no known focal adhesion kinase, but it contains two talin homologues (talA and talB) that have been shown to be important for multicellular development (Kreitmeier et al, 1995;Niewöhner et al, 1997;Tsujioka et al, 1999;Tsujioka et al, 2004). Deletion of talB results in mound arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the case of the gelation factor/α-actinin double mutant and the TalB mutant (Tsujioka et al, 1999;Witke et al, 1992), culmination in ∆forC cells could not be rescued by mixing them with wild-type cells. The lack of a synergy effect suggests that ∆forC cells were sorted out of wild-type cells within aggregates.…”
Section: Fh3 Is a Targeting Domain For Formin Family Proteinsmentioning
confidence: 80%
“…In some mutants, proper function can be restored through synergetic effects elicited by mixing the defective mutants with wild-type cells (Tsujioka et al, 1999;Witke et al, 1992). To test whether adding wild-type cells would rescue the developmental function of ∆forC cells, we allowed ∆forC cells to develop on MES agar plates after mixing them with wild-type cells at various ratios (Fig.…”
Section: Forc Knockout Cells Have Defects In Motility As Multicellulamentioning
confidence: 99%
See 1 more Smart Citation